Media entrepreneurship: a consensual definition (2017)
Media Entrepreneurship has been an ambiguous, unclear and controversial concept and despite of growing academic efforts in the last decade, it is still a poorly defined subject. This paper is an effort to fill this gap by providing a comprehensive definition of media entrepreneurship. Firstly, a literature review conducted and entrepreneurship, media, opportunity and innovation as building blocks of media entrepreneurship explained. Then by using of a mixed of bibliographic method and a Delphi method with multi-stage analysis process, a consensual definition of media entrepreneurship proposed. This definition integrates some key features of the emerging media environment such as distinction of content and platform, value delivery, opportunity development, non-monetary benefit, etc. It is expected that the findings of this research clear the ground for further researches in the field of media entrepreneurship